Efficacy of botanical lozenges in the treatment of chronic pharyngitis: a randomized controlled trial - Wu, Yi; Zhang, Feng; Kuang, Dan; Li, Dan; Yan, Jiai; Yang, Ju; Wang, Qinyue; Wang, Yingyu; Sun, Jing; Liu, Yiran; Xia, Yanping; Cao, Hong (Frontiers in Pharmacology, 2024)
Background: In clinical practice, antibiotics and/or inhaled or oral hormone preparations are the first line of treatment for chronic pharyngitis. However, this therapeutic regimen is not satisfactory enough. At present, medicinal plants as dietary supplements or functional foods are widely recognized for the treatment and prevention of different diseases.Purpose: This study aimed to evaluate the efficacy of the botanical lozenge made from several medicinal plant extracts in the treatment of chronic pharyngitis and its effects on patients' illness perception and adherence to treatment.: Patients with chronic pharyngitis were randomly assigned to the experimental group (n = 52) or the control group (n = 51). Patients were given botanical lozenges prepared from the extracts of medicinal plants such as Siraitia grosvenorii (Swingle) C.Jeffrey ex A.M.Lu & Zhi Y.Zhang [Cucurbitaceae; Siraitiae fructus], Lonicera japonica Thunb. [Caprifoliaceae; Lonicerae japonicae flos], Platycodon grandiflorus (Jacq.) A.DC. [Campanulaceae; Platycodonis radix], and Glycyrrhiza uralensis Fisch. ex DC. [Fabaceae; Glycyrrhizae radix et rhizoma] or placebos made of starch for 15 days. The improvement of pharyngeal symptoms and signs, illness perception, and adherence to treatment were evaluated at the end of the intervention.The total score of pharyngeal symptoms of patients in the experimental group (3.33 ± 2.33) was significantly lower than that in the control group (5.20 ± 2.93) (p < 0.01). In comparison to the control group (3.43 ± 1.43), the total pharyngeal signs score of patients in the experimental group (2.69 ± 1.59) was considerably lower (p < 0.01). The improvement rates of pharyngeal itching, dry throat, pharyngeal foreign body sensation, aggravation due to excessive speaking, and congestion of pharyngeal mucosa in the experimental group were 73.81, 67.50, 67.57, 65.22 and 44%, respectively, which were significantly higher than those in the control group (p < 0.05). In addition, patients taking botanical lozenges had better illness perception and adherence to treatment than those taking placebos (p < 0.05). Patients with low adherence to treatment showed less personal control, concerns, and understanding of chronic pharyngitis (p < 0.05).Conclusions: Botanical lozenges not only aided patients in recovering from chronic pharyngitis but also improved their positive perceptions and adhere to treatment.